Investigation of Job Satisfaction and Burnout of Visual Arts Teachers - Kara, Sema (ISTES Organization, 2019)
In this study, it is aimed to examine the job satisfaction and burnout of visual arts teachers in terms of some variables. Based on the causal comparative method; job satisfaction and burnout of visual arts teachers were compared according to variables such as gender, age, marital status, professional seniority and school type. In addition, the relationship between job satisfaction and professional burnout of visual arts teachers was tried to be explained with correlational research design. The sample of the study consists of 308 visual arts teachers working in Ankara, Istanbul, Konya, Mersin, Eskisehir and Sanliurfa. The Maslach Burnout Inventory and Minnesota Job Satisfaction scales were used to collect the research data. According to the findings of the research, job satisfaction and burnout of visual arts teachers show significant differences according to gender, marital status, professional seniority and school type. In addition, there is a significant but negative relationship between visual arts teachers’ job satisfaction and burnout.
Keywords: 4. Education; 8. Economic growth